Ultra Wideband Noise Channel Measurement using a Vector Network Analyzer - Ahmed Alshabo; Peter James Vial; Montserrat Ros; David Stirling; Muhammad Abu Bakar Sidik (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
In this paper, we analyze the measurement of ultra wideband (UWB) noise channels in different indoor environments. All measurements are done using a vector network analyzer (VNA) which allows us to measure the noise channel transfer functions. We find that the noise power of the system is decreased by increasing the intermediate frequency (IF) bandwidth which leads to an increase in time taken to perform measurements of the channels. Also, we measure the environmental noise power and find that it is slightly affected by fluorescent light sources inside the measurement environments. In addition, we find that the environmental noise is decreased when enclosed in a Faraday cage (steel shed), within an intense multipath measurement environment. As secondary application, we show how a frequency detection device can be used to re-adjust a maladjusted frequency selection on a remote controller for a garage door, in presence of environmental noise power.